How to increase COVID-19 vaccine uptake among children? determinants associated with vaccine compliance - Hoshen, Moshe; Shkalim Zemer, Vered; Ashkenazi, Shai; Grossman, Zachi; Gerstein, Maya; Yosef, Noga; Cohen, Moriya; Cohen, Herman Avner (Frontiers in Pediatrics, 2023)
Objective Three aims: to elucidate determinants associated with COVID-19 vaccine uptake in children and the association with parental vaccination; to compare rates of PCR-positive SARS-CoV-2 results between vaccinated and unvaccinated children; to estimate the rate of parental COVID-19 vaccination and its association with the vaccination rate of their children. Methods We performed a retrospective chart review of all children aged 5–11 years registered at a central district in Israel from November 21st, 2021 to April 30th, 2022, and characterized COVID-19 vaccinated vs. unvaccinated individuals. Data retrieved from the electronic medical files included: demographics [age, gender, sector, socioeconomic status (SES)]; COVID-19 vaccination (first and second doses) and influenza vaccination status; co-morbidities; and parental vaccinations for COVID-19. We divided the population into three distinct demographic groups: non-ultra-orthodox Jews (43,889 children), ultra-orthodox Jews (13,858 children), and Arabs (4,029 children). Results Of the 61,776 children included in the study, 20,355 (32.9%) received at least one dose of the COVID-19 vaccine. Vaccination rates were similar amongst males and females and were higher in children aged 9–11 years compared to children aged 5–6 years. Multivariate analysis identified five independent determinants that were significantly (p < 0.001) associated with low vaccination rates: Arab and ultra-orthodox sectors (odds ratios: 0.235 and 0.617, respectively); children aged 5–8 years; children of low SES; and children who had not received previous seasonal influenza vaccination. Relatively high vaccination rates were noted amongst children with the following medical co-morbidities: treatment with biological agents (42.9%); solid tumor transplantation (42.9%); type 1 diabetes mellitus (38.5%), asthma (38.2%), and attention deficit and hyperactivity disorder (ADHD) (37.6%). Regarding the uptake of two vaccine doses among children with co-morbidities, it was highest in those with type 1 diabetes mellitus, heart failure, treatment with biological agents, asthma and obesity. Conclusion This study highlights several pediatric sub-populations with low and high vaccine uptake. It is essential to focus on determinants associated with low vaccination rates.